Introduction to the Special Issue: Way Out Voices: A Phenomenology of Interbeing - Hagens, Bethe (Anthropology of consciousness, 2017)
Interbeing is a foundational teaching of Thiền Sư (Zen master) Thích Nhất Hạnh, beloved Vietnamese Buddhist monk and peace activist who has worked closely with Chân Không, an expatriate Vietnamese Buddhist nun. Together they founded Plum Village retreat center in the Dordogne region of France. This volume of invited essays – taken as a whole – reveals the inspirational power of the word interbeing as a focus for creating common ground within scholarship for voices not so often heard. Metaphorically, this phenomenology is what Nhất Hạnh might call a “hugging meditation.”